Palm Kernel Shell as a Source of Functional Biochar: A Review of Recent Scientific Progress - Margareta N. Cahyanti; Dewi K.A. Kusumahastuti; Sri Hartini (Postgraduate, University of Mataram, 2025)
This report examined the research trends in production and application of biochar derived from palm kernel shells (PKS) over the past decade. A Systematic Literature Review (SLR) was conducted on 63 articles indexed in Scopus between 2015 and 2025, with bibliometric mapping performed using VOSviewer. From 2015, the number of publications on PKS biochar grew gradually, reaching a peak in 2020 and 2023. Through the use of keyword co-occurrence mapping, four significant clusters of PKS biochar research were identified. These clusters primarily dealt with pyrolysis, activated carbon, biofuels, and biomass usage as main themes. The term